DYSPLASTIC RECTAL POLYP (LOW GRADE) - Kasalović, Mladen (Acta medica Medianae, 2023)
Villous adenoma is a non-cancerous growth in the colon. It develops from the cells that cover the inner surface of the large intestine. These adenomas can develop anywhere along the colon, from the cecum to the rectum. All villous adenomas are associated with an increased risk of developing colon cancer called adenocarcinoma over time. Polyps can be sessile or pedunculated and vary in size. The incidence of polyps ranges from 7−50%; a higher incidence refers to very small polyps (which are usually hyperplastic or adenomas) and are found as an incidental finding at autopsy.A 72-year-old female patient K. D. presented because of bleeding during defecation and a change of the size of an apple that used to "fall out" from the anus during defecation. She reported to have experienced this change for more than a year and the bleeding from it in the last few weeks. She used suppositories, but there were no changes in the local findings. Further, she performed a colonoscopy, where a pale pink mucosa was seen, with normal findings, except for 3−4 cm, where there was a cauliflower-like change on the stalk, partially covered with fibrin deposits, hyperemic.According to the data, the combined risk of dysplasia/malignancy is about 83% with a 50% risk of dysplasia and overt malignancy in 33% of cases of giant rectal villous adenomas larger than 8 cm.
Keywords: tubulovillous adenoma, lifestyle, bleeding, cancer